The CeNGEN Project: The Complete Gene Expression Map of an Entire Nervous System - Hammarlund, Marc (Neuron, 2018)
Differential gene expression defines individual neuron types and determines how each contributes to circuit physiology and responds to injury and disease. The C. elegans Neuronal Gene Expression Map & Network (CeNGEN) will establish a comprehensive gene expression atlas of an entire nervous system at single-neuron resolution.